2000
DOI: 10.4049/jimmunol.164.7.3913
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a CD8 T Cell That Can Independently Mediate Autoimmune Diabetes Development in the Complete Absence of CD4 T Cell Helper Functions

Abstract: Previous work has indicated that an important component for the initiation of autoimmune insulin-dependent diabetes mellitus (IDDM) in the NOD mouse model entails MHC class I-restricted CD8 T cell responses against pancreatic β cell Ags. However, unless previously activated in vitro, such CD8 T cells have previously been thought to require helper functions provided by MHC class II-restricted CD4 T cells to exert their full diabetogenic effects. In this study, we show that IDDM development is greatly accelerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
124
2
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(131 citation statements)
references
References 43 publications
4
124
2
1
Order By: Relevance
“…[1][2][3][4] However, exceptions have been reported in MHC-I-restricted alloantigen- 5 and autoantigen-specific 6,7 TCRtransgenic mice, in which there was no differentiation bias for CD8 1 T cells. In these transgenic mice, most of the CD4 1 T cells expressed an MHC-I-restricted transgenic TCR, which could be detected by specific anti-TCR antibodies, and an additional rearranged endogenous MHC-II-restricted TCR through which the CD4 1 T cells could be positively selected to maintain a normal ratio of CD4 1 to CD8 1 T cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] However, exceptions have been reported in MHC-I-restricted alloantigen- 5 and autoantigen-specific 6,7 TCRtransgenic mice, in which there was no differentiation bias for CD8 1 T cells. In these transgenic mice, most of the CD4 1 T cells expressed an MHC-I-restricted transgenic TCR, which could be detected by specific anti-TCR antibodies, and an additional rearranged endogenous MHC-II-restricted TCR through which the CD4 1 T cells could be positively selected to maintain a normal ratio of CD4 1 to CD8 1 T cells.…”
Section: Introductionmentioning
confidence: 99%
“…By binding to MHC-I molecules on antigen-presenting cells, CD8 can strengthen MHC-I-restricted TCR signaling. 8,9 Although it was discovered by antibody staining in several MHC-I-restricted TCRtransgenic mice that the CD4 1 T cells expressed MHC-I-restricted transgenic TCRs, 5,6,7 so far, there has not been direct proof to determine whether the MHC-I-restricted transgenic TCRs on the CD4 1 T cells bind to the MHC-I/peptide complex.…”
Section: Introductionmentioning
confidence: 99%
“…Starting with the pioneering work of Rammensee and colleagues [5,9], Kd has been widely studied, and Kd-specific immune responses described in a number of experimental systems. These include CD8 T cell responses: (1) against viral and bacterial pathogens [6,[19][20][21][22]; (2) in the NOD mouse model of diabetic autoimmunity [23][24][25][26][27]; and, (3), to tumor antigens [28][29][30][31]. Despite these many studies, the number of identified endogenously processed peptides selected by Kd is small.…”
Section: Introductionmentioning
confidence: 99%
“…A third islet-reactive, pathogenic NOD CTL, although initially thought to be specific to a dystrophia myotonica kinase, amino acids 138-146 (DMK [138][139][140][141][142][143][144][145][146] ) peptide, is actually reactive to insulin. [23][24][25] Interestingly, the relative distribution in the infiltrate of T cells varies considerably among individual mice, defining a unique immunological signature. [20][21][22][23] CD8 T cells reactive to glutamic acid decarboxylase (GAD65)-especially GAD65, amino acids 546-554 (GAD65 546-554 )-have also been identified in the NOD mouse.…”
Section: Introductionmentioning
confidence: 99%